Statistical analysis of electronic excitation processes: Spatial location, compactness, charge transfer, and electron‐hole correlation1. Issue 21 (29th June 2015) - Plasser, Felix; Thomitzni, Benjamin; Bäppler, Stefanie A.; Wenzel, Jan; Rehn, Dirk R.; Wormit, Michael; Dreuw, Andreas
<x xml:space="preserve">Abstract</x> We report the development of a set of excited‐state analysis tools that are based on the construction of an effective exciton wavefunction and its statistical analysis in terms of spatial multipole moments. This construction does not only enable the quantification of the spatial location and compactness of the individual hole and electron densities but also correlation phenomena can be analyzed, which makes this procedure particularly useful when excitonic or charge‐resonance effects are of interest. The methods are first applied to bianthryl with a focus on elucidating charge–resonance interactions. It is shown how these derive from anticorrelations between the electron and hole quasiparticles, and it is discussed how the resulting variations in state characters affect the excited‐state absorption spectrum. As a second example, cytosine is chosen. It is illustrated how the various descriptors vary for valence, Rydberg, and core‐excited states, and the possibility of using this information for an automatic characterization of state characters is discussed. © 2015 Wiley Periodicals, Inc.